2011
DOI: 10.1007/s00468-011-0583-5
|View full text |Cite
|
Sign up to set email alerts
|

Branching of annual shoots in common walnut (Juglans regia L.) as affected by bud production and indol-3-acetic acid (IAA) content

Abstract: Relationship of bud production (axillary and terminally) of annual shoot (1Y) and/or the content of budderived indol-3-acetic acid (IAA) to branching of the 1Y was studied in common walnut (Juglans regia L.), cvs. Franquette and Lara. Cultivar-related branch architecture was determined. Lara tended to branch more densely than Franquette (53 vs. 42%). Significantly more fruiting offspring shoots (FO) than vegetative ones (VO) grew-out per 1Y in both cultivars, whereas the ratio FO/VO of Lara exceeded that of Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, development of sylleptic shoots has been previously related to rapid parent shoot growth rate in peach [Prunus persica (Génard et al, 1994;Hipps et al, 1995)]; thus, more rapid growth rates may have occurred in this cultivar than in the others. In addition, the acrotonic, mesotonic, or basitonic distribution of branching along the shoots have been explained as the result of the equilibrium of auxin and cytokinins (Cook et al, 2001;Solar et al, 2011;Tworkoski and Miller, 2007;Wilson, 2000). For example, strong acrotony has been reported when greater cytokinin content was concentrated in distal shoot parts before the basal part of the shoots in apple (Cook et al, 2001) and less branching was observed with higher concentrations of auxin in walnut shoots [Juglans regia (Solar et al, 2011)].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, development of sylleptic shoots has been previously related to rapid parent shoot growth rate in peach [Prunus persica (Génard et al, 1994;Hipps et al, 1995)]; thus, more rapid growth rates may have occurred in this cultivar than in the others. In addition, the acrotonic, mesotonic, or basitonic distribution of branching along the shoots have been explained as the result of the equilibrium of auxin and cytokinins (Cook et al, 2001;Solar et al, 2011;Tworkoski and Miller, 2007;Wilson, 2000). For example, strong acrotony has been reported when greater cytokinin content was concentrated in distal shoot parts before the basal part of the shoots in apple (Cook et al, 2001) and less branching was observed with higher concentrations of auxin in walnut shoots [Juglans regia (Solar et al, 2011)].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cambial activity is associated with changes in IAA/ABA, and ABA might play a key role in vascular cambium dormancy in Eucommi aulmoides (Mwange et al, 2005). Branching of annual shoots in the common walnut (Juglans regia) is affected by IAA concentration (Solar et al, 2011). In the present study, we did not find a strong relationship between IAA concentration and cell length (P > 0.05), but cell length was positively correlated with IAA/ABA (R = 0.518, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%